Training and Mentoring on the Use of Information and Communication Technology (ICT) in Supporting the Implementation of Learning at UPT SD Negeri 342 Gresik - Pance Mariati; Afib Rulyansah; Sri Hartatik; Nafiah; Sunanto (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2022)
Abstract: UPT SD Negeri 342 is one of the schools in Sangkapura Bawean District, which is located in the mountains. This school has very minimal facilities compared to other schools in the area. The implementation of online learning, administration and the use of technology-based learning media are not maximally implemented in these schools. Therefore, training and assistance in the use of information and communication technology is carried out. Participants consisted of 8 teachers and 36 students. The training is carried out face-to-face, followed by online and offline mentoring. The training materials presented were Augmented Reality (AR) in the Arloopa application, the use of The Physics Education Technology (PhET) for virtual student practicums, mentimeters, and zoom meetings. After the work program is implemented, an evaluation will be held to identify capacity building and its strengths and weaknesses as material for improvement in the next implementation. The results of the training showed that the ICT skills of teachers and students increased from previously unable to become able. All the teachers attended the training and participated enthusiastically. The material presented can be understood clearly and participants can apply it independently. They just need habituation to better master the material that has been given. This training activity had a good impact on improving the ICT skills of teachers and students at UPT SD Negeri 342 Gresik.